Assessment of High Sensitivity C.Reactive Protein in male patients with metabolic syndrome and atherosclerosis complications - Khazaal, Faris Abdul Kareem; Fadhil, Safaa Hassan; qunaid, Hamza (AL-Kindy College Medical Journal, 2012)
Background: syndrome X or metabolic syndrome is a collection of multiple diseases mainly visceral obesity , hypertriglyceridemia , decrease HDL level, hypertension and elevated fasting blood glucose that lead to accelerated atherosclerosis through multiple mechanisms, one of the most important is increase inflammation of the vessels manifested by elevated high sensitivity C reactive protein (hs-CRP).Objective: The aim of the study was to assess the prevalence of elevatedhs CRP in people with metabolic syndrome and atherosclerosis complication (IHD, Cerebrovascular disease, peripheral vascular disease) and metabolic syndrome without these complication.Patients and methods:;This is a cross sectional study carried out in Diabetic referral center in Baghdad al-rusafa extended from November 2009 to March 2010 for 84 male patients with metabolic syndrome ,aged 40-70 years, clinical features ,anthropometric and biochemical measurement (BP, Waiste circumference, BMI, HDL, LDL, TG, BG, hs CRP) were recorded and metabolic syndrome diagnosis was made according to IDF definitionResults: The 84 patients with metabolic syndrome divided in to two groups the first 35 patients clinically complicated atherosclerotic group were 30 patients high risk 85% and 5 patients low risk 15%. The second 49 patients (clinically uncomplicated atherosclerotic) group were 30 patients high risk 61% and low risk 19 patients 39%, and tabulated with the p.value was (0.014).These results tabulated with the following parameters ,waist circumference (abnormally high p.value was 0.05, normal p.value was 0.49) ,blood pressure (hypertension p.value was 0.05 and normal blood pressure p.value was 0.58),age(middle age p.value was 0.007 and elderly age p.value was 0.29) and BMI(less than 25g/kg p.value was 0.39 and more than or equal to 25 g/kg p.value was 0.08).Conclusion: The values of hs-CRP are high in most patients with metabolic syndrome but are higher in patients with atherosclerotic complications than those without .specially elevated in those with hypertension ,middle age group, increasing waist/hip ratio with significant p.value,and in high BMI but with insignificant p.value.Key words : (HS-CRP metabolic)